Hypobaric hypoxia aggravates neuroinflammation in ligature-induced periodontitis mice via the STAT3 signaling pathway - Chen, Lu; Zhang, Jiayi; Fei, Xuechao; Wang, Jiajing; Gao, Jiayue; Yue, Xiangpei; Jiang, Yaqun; Shi, Zibi; Zhang, Shaojie; Jiang, Xiufang; Chang, Wenyue; Dai, Zhonghua; et al. (Frontiers in Immunology, 2025)
Background and purposeStudies have shown that inflammation is a key risk factor for altitude sickness in hypobaric hypoxia environments. Periodontitis, a common oral disease, is prevalent among many individuals. This study aimed to investigate the onset and progression of neuroinflammation in mice with ligature-induced periodontitis under hypobaric hypoxia and to explore the potential underlying mechanisms.MethodsC57BL/6J mice were randomly divided into four groups: control (Con), hypobaric hypoxia (HH), periodontitis (P), and periodontitis combined with hypobaric hypoxia (PHH), which were then placed in a hypobaric hypoxia chamber for 1, 3, and 5 days. The expression of inflammatory cytokines was assessed by qPCR or ELISA. Anxiety-related behavior and memory abilities were evaluated by behavioral tests. The activation of microglia and astrocytes in the hippocampus and cortex was assessed by immunofluorescence.ResultsOur results demonstrated that one day of exposure to hypobaric hypoxia in mice with periodontitis significantly exacerbated periodontal inflammation, peripheral inflammation, and neuroinflammation. Specifically, hippocampal microglia in these mice were activated following brief exposure to hypobaric hypoxia. Furthermore, the STAT3 signaling pathway was markedly activated, playing a crucial role in mediating the intensified neuroinflammation observed in periodontitis model mice subjected to one day of hypobaric hypoxia.ConclusionOur data highlight the exacerbating effect of hypobaric hypoxia on neuroinflammation in periodontitis model mice, mediated through the activation of the STAT3 signaling pathway. These findings provide important insights and considerations for individuals with periodontitis who are planning to travel to high-altitude regions.